The effect of anxiety on working memory and language abilities in elementary schoolchildren with and without Additional Health and Developmental Needs - Pickering, Hayley E.; Parsons, Carl; Crewther, Sheila G. (Frontiers in Psychology, 2022)
Although excessive childhood anxiety is recognized as a significant public health, education, and socioeconomic concern, the specific effects of such anxiety on language development and working memory, particularly visual working memory, are relatively unknown. Thus, this study aimed to examine parent-reported trait anxiety, parent-reported functional language (daily communication skills), and clinical measures of non-verbal intelligence, receptive and expressive vocabulary, phonological awareness, and visual and auditory-verbal short-term and working memory in elementary schoolchildren. The final sample included 41 children categorised as Additional Health and Developmental Needs (AHDN) due to medical, neurodevelopmental, or educational concerns, and 41 age- and IQ-matched neurotypical (NT) children, aged 5- to 9-years. Results showed that 26% of all children in our entire sample (AHDN and NT) experienced moderate, subclinical anxiety (as reported by parents), and that AHDN children were 10.5 times more likely to experience high anxiety than the NT group (odds ratio). Parents of AHDN children reported lower functional language in their children than parents of NT children. Cognitive testing indicated that the AHDN group also had poorer visual and auditory-verbal working memory than the NT group. Further, High Anxiety children (drawn from both AHDN and NT groups) showed poorer parent-reported function language skills, and lower visual and auditory-verbal working memory capacities. Our findings are among the first to confirm that the presence of high parent-rated trait anxiety is associated with reduced visual working memory in children, which is consistent with biological and theoretical expectations of the impact of anxiety on visually-driven, goal-directed attention and working memory. Our results regarding the high prevalence of subclinical anxiety in both ADHD and neurotypical children highlight the need for early assessment of anxiety in all schoolchildren, especially those classified as AHDN.